PRODUCT QUALITY AND PRICE PERCEPTION BUYING DECISION AGAINST SALONPAS PAIN RELIEF PATCH IN HYPERMART DAAN MOGOT WEST JAKARTA - Tyas, Ari Anggarani Winadi Prasetyoning; Wulandari, Desy (Journal of Management and Business, 2015)
In this research aims to analyze the influence of the quality product (X1) and perceived price (X2) on purchase decisions (Y) toward Salonpas Pain Relief Patch (Case Study in Hypermart Daan Mogot West Jakarta). The data used in this research is primary data obtained from the answers of the respondents who had bought and feel Salonpas Pain Relief Patch. The sampling technique used in this research was a non-probability sampling, whereas the sample collection method can be done by purposive sampling method and the method of determining the number of samples generated using the MOE formula of 100 respondents. Respondents in this study is that consumers are shopping in Hypermart Daan Mogot West Jakarta ever purchased and feel the Salonpas Pain Relief Patch. This research uses multiple linear regression method. Research results show that the quality of products (X1) has a significant influence on purchasing decisions (Y), and price perception has a significant influence on purchasing decisions (Y), but it also results showed that the quality of products (X1) and perceived price (X2) jointly have a significant impact on the purchase decision.